High-performance liquid chromatographic method for the analysis of fluconazole in pharmaceutical preparations - Duangsamorn Limpiti (2018)
High-performance liquid chromatographic method was developed for the analysis of fluconazole in pharmaceutical preparations. The analyzed drug was separated on a reversed-phase column [Hypersil ODS column (120 x 46 mm, 5 μm particle size)], using a mobile phase containing methanol: 10 mM pH 7.0 phosphate buffer (50:50) with UV detection at 260 nm. The proposed method is specific, sensitive, reproducible and reliable. It can be successfully applied as a stability-indicating method for the determination of fluconazole in pharmaceutical preparations. With a run time of less than 2 minutes, the method is rapid and easy to use for routine analysis of fluconazole in pure form and dosage form as well as for its dissolution testing.